Vitamins and hormones : advances in research and applications. Volume 19 - Harris, Robert S. (Robert Samuel), 1904-1983.; Ingle, Dwight J. (Dwight Joyce), 1907-1978.; ScienceDirect eBooks (New York : Academic Press, 1961)
VITAMINS AND HORMONES V19.
VI. The Parathyroids and Calcium HomeostasisVII. Biologic Assay of the Parathyroid Hormone; VIII. Pathologic Physiology of the Parathyroid Glands; References; Chapter 6. Extra-adrenal Actions of Adrenocorticotropin; I. Introduction; II. Extra-adrenal Metabolic Actions of ACTH; III. Melanocyte-stimulating Activity of ACTH; IV. Other Reported Extra-adrenal Actions of ACTH; V. Extra-adrenal Actions of Endogenous ACTH; VI. Relation of ACTH Structure to Its Adrenal and Extra-adrenal Actions; VII. Significance of the Extra-adrenal Actions of ACTH; References.
Includes bibliographical references and indexes.
Print version record.
Elsevier
Keywords: Vitamins -- Research; Hormones -- Research; MEDICAL -- Nutrition; Hormones -- Research; Vitamins -- Research; Electronic books